2018
DOI: 10.31529/sjms.2018.4.2.9
|View full text |Cite
|
Sign up to set email alerts
|

Internal Factors, External Factors and Bank’s Profitability

Abstract: A developed banking sector provides the impetus for the economy to grow. However, in order to maintain financial stability and sustain negative shocks, it is important to understand the factors that influence the profitability of banks. The aim of the study was to analyse the effect of internal and external factors on the profitability of banks in Pakistan for the period 2007-2015. Fixed effects model was used to analyse the effect of internal and external factors on the profitability of banks in Pakistan. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…These are factors that are beyond the control of the banks and they include the macro‐economic variables (Al‐Homaidi et al., 2018; Rehman et al., 2018) such as Economic Growth Rate, and Inflation level in a country. These variables are now explained below:…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…These are factors that are beyond the control of the banks and they include the macro‐economic variables (Al‐Homaidi et al., 2018; Rehman et al., 2018) such as Economic Growth Rate, and Inflation level in a country. These variables are now explained below:…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Several researchers together with Jaber and Al-Khawaldeh (2014), Berhe (2017), Rehman et al (2018), Yuksel et al (2018), Assfaw (2018), Makkar and Hardeep (2018), Al-Homaidi et al (2018), Bhattarai (2018), Supriyono and Herdhayinta (2019), Al-Harbi (2019), etc., have conducted research to analyze the determinants of the profitability of banks in different countries across the world. A number of studies have also been done in Bangladesh with same focal point such as Sufian and Kamaruddin (2012), Mizan et al (2013), Rahman and Akhter (2015), Mahmud et al (2016), Banna et al (2017), Siddique et al (2017, Liza (2017), Matin (2017), Islam and Rana (2017), , Lee and Iqbal (2018), Hossain and Khalid (2018), and Hassan and Ahmed (2019).…”
Section: Justification Of the Studymentioning
confidence: 99%
“…Thus, profitable banks will ensure the continuity of economic growth as well as the stability of the financial system (Al-Harbi, 2019). However, to maintain financial stability and sustain negative shocks, it is important to understand the factors that influence the profitability of banks (Rehman et al, 2018). On the other hand, banking business is directly associated with trust factor (Babu & Choudary, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Some of the results of this study support previous research, such as research conducted by Ebenezer et al, (2019) at 63 commercial banks in ASEAN-5 countries during the period 2009-2017, using the regression of panel data, found that the Loan to Deposit Ratio (LDR) negatively affected bank risk. Rehman et al, (2018) stated that a more concentrated banking market will decrease competition and at the same time will provide better access to bank deposits and loans, thus lowering risk. Jabra, Mighri and Mansouri (2017) conducted research in Eastern Europe and Western Europe, using panel data from 280 banks during the period 2005 to 2015, finding that excessive volatility in international financial markets, internal and macroeconomic factors can have a positive and negative effect on bank risk.…”
Section: Table 4 the Results Of Panel Data Regression With Random Effects Model Onmentioning
confidence: 99%